The digital economy, industrial structure upgrading, and carbon emission intensity —— empirical evidence from China's provinces - Hong Chang; Qingyi Ding; Wanzheng Zhao; Na Hou; Wenwen Liu (Energy Strategy Reviews, 2023)
The digital economy plays a pivotal role in assisting the world in tackling climate change. This paper explores the intrinsic mechanism of the digital economy on carbon emissions intensity. Initially, it scrutinizes the suppressive effect of the digital economy on carbon emissions intensity, as well as the mediating mechanism of industrial structure upgrading, on a theoretical level. Subsequently, it utilizes provincial panel data from China between 2010 and 2019 to investigate the quantitative relationship between the digital economy and carbon emissions intensity empirically. The results revealed that, firstly, the digital economy significantly diminishes carbon emissions intensity; secondly, it confirms the significant mediating role of industrial structure upgrading; thirdly, increased levels of economic development, market openness, human capital, technological advancement, and urbanization all have constructive moderating effects on the carbon emission reduction facilitated by the digital economy; fourthly, the influence of the digital economy on carbon emission intensity has spatial spill-overs. This paper contributes an integrated analytical framework and method for studying the digital economy, industrial structure upgrading, and carbon emissions intensity. Furthermore, it offers valuable insight and suggestions for policy-making concerning the digital economy's contribution to carbon emissions reduction.